Electrochemotherapy in the Locoregional Treatment of Metastatic Colorectal Liver Metastases: A Systematic Review - Pierluigi Barbieri; Alessandro Posa; Valentina Lancellotta; David C. Madoff; Alessandro Maresca; Patrizia Cornacchione; Luca Tagliaferri; Roberto Iezzi (Current Oncology)
Background: The global incidence of secondary liver cancer is rising due to multiple risk factors, presenting significant challenges in public health. Similarly, colorectal cancer (CRC) remains a leading cause of cancer-related mortality with the development of frequent liver metastases. Surgical resection of CRC liver metastases is only suitable for a limited subset of patients, necessitating alternative nonsurgical treatments such as electrochemotherapy (ECT); Methods: This review adhered to the S.P.I.D.E.R. framework. Systematic searches of PubMed, Cochrane, and Scopus databases were conducted for studies published between 2003 and 2023, following PRISMA guidelines. Inclusion criteria were full-text clinical studies in English focusing on ECT-treated CRC liver metastases, excluding reviews, editorials, and non-clinical papers. The GRADE approach was utilized to assess evidence quality, considering study limitations, consistency, and other factors; Results: From 38 identified articles, 4 met the inclusion criteria, encompassing 78 patients and 128 treated lesions. The studies demonstrated variability in design and follow-up duration (3–11 months). Complete response (CR) rates ranged from 33.3% to 63.0%, while progression disease (PD) rates were high, ranging from 23.0% to 55.6%. Median overall survival (OS) spanned 11.3 to 29.0 months. No severe ECT-related complications were reported. Conclusions: ECT appears to be a safe and effective modality for the treatment of CRC liver metastases, especially for lesions unsuitable for other ablative techniques. Further prospective and randomized studies are essential to better define the role of ECT in managing CRC liver metastases and to compare its efficacy with other ablative methods.